Considerações sobre uma psicologia do desenvolvimento humano a partir da fenomenologia antropológica de Edith Stein - Menegi, Beatriz Oliveira (2022)
Human Development is a field of study of Psychology, elaborated by several theories, it has strong historical and biological bases. However, none of these theories encompasses the human in its specificity, as well as there are no phenomenological theories of development. We aim in this study to outline some theoretical contributions of how Edith Stein's Phenomenological Anthropology can support a "Psychology of Human Development". To this end, three independent studies were conducted. In Study I, we sought to know how phenomenologically based theories of human development are being conceived and used in Psychology through a narrative literature review with a database search, in which 14 articles composed the analysis. The studies found were descriptively characterized and interpretively analyzed in two units of meaning based on the Giorgi’s phenomenological analysis. We conclude the need to explore the still emerging theme and the lack of empirical studies, as well as the foundation of a Developmental Psychology with properly phenomenological bases. In Study II, the positivist influence on the psychological sciences was problematized, which entails to a reductionist and naturalist view, as well as presents the criticism of Phenomenology to this model, which highlights the need for a view of Development that considers the human in its totality and specificity. A qualitative-bibliographic research was carried out that explored Stein's life and work, as well as her contributions about the structure of the human person through her phenomenological-anthropology. Stein elaborated an integral vision of the human, composed of body-psyche-spirit. We approach in the study the psychic causality and its relationship with the natural world, but the importance of not limiting a theory of development to naturalism, since the spiritual dimension is governed by motivation, a dimension that is characterized by the specifically human. It is concluded in this study that even though Stein has not, in her writings, discussed human development, we find in her works, mainly her pedagogical texts, soil to support a theory of development. Based on these assumptions, in Study III, we sought to think of a Developmental Psychology that considers what is properly human, through a qualitative-bibliographic research. Given the tripartite condition of the human constitution, we have the spirit as the specifically human, which differentiates man from the animal, and even though both are endowed with instincts, only the human has the freedom to accept or reject their impulses. We must therefore consider human specificity in a theory of development, such as motivation and freedom. Considering the specifically human, we tried to sketch a phenomenological developmental psychology that encompassed the period from the birth to the “awakening”. Through the corporeity and the maternal relationship, the baby incorporates the world, its initial instincts allow its survival and development so that it later awakens as a human subject. We conclude, through the three studies, that there is a gap in a phenomenological view of development and in a theory that considers the human being in its integrality, what we point out the bases for subsequent researchers about human development in phenomenological perspective.